Policy Analysis in Improving the Quality of Health Services: A Literature Study - Sri Hajijah Purba; Azzahra Khairani Siregar; Nur Afini Turnip; Amanda Aqiilah; Lisca Amalia Putri Br. Sinaga; Rintan Arzeti (Universitas Muhammadiyah Palu, 2026)
he quality of healthcare services is a crucial indicator of the success of the national healthcare system. Various healthcare policies in Indonesia continue to be developed to improve access, service quality, and public satisfaction. This research employed a literature review with a qualitative descriptive approach through the Google Scholar database and other scientific sources, using keywords such as health policy, BPJS, JKN, healthcare service quality, and health policy. The articles used were published between 2022 and 2026. The search identified 50 articles, which were then narrowed down to 25 based on topic relevance and source credibility, resulting in 18 articles analyzed in this study. The results indicate that the JKN and BPJS Kesehatan programs play a role in improving access and quality of public healthcare services. Service quality is influenced by the competence of healthcare workers, service facilities, management systems, communication, and the use of healthcare technologies such as telemedicine and electronic medical records. However, policy implementation still faces various obstacles, including limited healthcare workers, uneven distribution of facilities, long service queues, and complex administration. The novelty of this research lies in the integration of Edward III's policy implementation theory with an analysis of healthcare service quality and the digital transformation of healthcare services in Indonesia.